2008
DOI: 10.4025/actascitechnol.v30i1.3245
|View full text |Cite
|
Sign up to set email alerts
|

Técnicas moleculares aplicadas à microbiologia de alimentos

Abstract: RESUMO.A partir da década de 80, as técnicas moleculares começaram a ser utilizadas como uma alternativa aos métodos fenotípicos, tradicionalmente, utilizados em microbiologia de alimentos. Foi acelerada esta substituição com advento da descoberta da reação em cadeia da polimerase (polymerase chain reaction -PCR). Este artigo tem por objetivo revisar as principais técnicas moleculares utilizadas como ferramentas na microbiologia de alimentos, desde as, inicialmente, desenvolvidas, como a análise do perfil plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 9 publications
0
11
0
8
Order By: Relevance
“…Cohen et al (1996) observed that positive samples in PCR were negative in culture; however the majority of the positive cultures were also positive in PCR. Although traditional techniques of culture and bacterial identification are used as official for analysis, it is fundamental to complement molecular techniques, since they present a higher sensitivity in a shorter time (Gandra et al 2008). Samples from five animals that were PCR positive (samples from the TT broth) were not confirmed by bacteriological culture which may indicate different differentiated bacterial profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Cohen et al (1996) observed that positive samples in PCR were negative in culture; however the majority of the positive cultures were also positive in PCR. Although traditional techniques of culture and bacterial identification are used as official for analysis, it is fundamental to complement molecular techniques, since they present a higher sensitivity in a shorter time (Gandra et al 2008). Samples from five animals that were PCR positive (samples from the TT broth) were not confirmed by bacteriological culture which may indicate different differentiated bacterial profiles.…”
Section: Discussionmentioning
confidence: 99%
“…The cost of most PCR techniques is relatively high; however, there are low cost systems that involve a single PCR reaction, followed by electrophoresis in agarose or polyacrylamide gel, such as ARMS-PCR (Amplification Refraction Mutation System), which makes the technique more accessible (Gandra et al, 2008;Guimarães et al, 2009). ARMS-PCR differs from an RFLP-PCR for allele determination since it does not require the use of a restriction enzyme in order to cleave the amplified DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Various PCR modifications have been described, among which Rep-PCR, which involves the amplification of areas between repetitive elements, generating specific profiles (Gandra et al, 2008). This technique allows the determination of the origins of pathogenic microorganisms' contamination in food catering services such as those of hotels, thus filling the gap caused by the lack of information in this field of activity.…”
Section: Introductionmentioning
confidence: 99%